Progress of diagnosis and treatment decisions in stage Ⅲ/Ⅳ periodontitis - CHEN Xu, LI Lu, WANG Xiaoqian, WANG Tianyao, XU Yan (Kouqiang yixue)
In 2018, a consensus on the new international classification of periodontal diseases and peri-implant diseases was jointly published by the American Academy of Periodontology (AAP) and European Federation of Periodontology (EFP), which divided periodontitis into stagesⅠ-Ⅳ. The diagnosis and treatment of stage Ⅲ/Ⅳ periodontitis are the focus and difficulty in clinical practice. Developing standardized clinical decision-making for the diagnosis and treatment of stage Ⅲ/Ⅳ periodontitis can help patients with this condition achieve better plaque control, maintain healthy periodontal status and restore chewing function and aesthetics. Based on the EFP S3 level clinical guidelines for the treatment of stage Ⅰ-Ⅲ and stage Ⅳ periodontitis, combined with the new international classification of periodontal diseases and peri-implant diseases in 2018 and the Chinese expert consensus on the diagnosis of severe periodontitis in 2017, this article elaborates clinical diagnosis and treatment decisions for stage Ⅲ/Ⅳ periodontitis, aiming to provide reference for clinical application practice.